ELEMENTS AND PERSUASIVE LANGUAGE STRATEGIES IN BMTA BUS AND BMTA PRIVATE JOINT BUS ADVERTISING - Rojtananan, Korapat; Charoonpaisal, Pakawadee; Bhodthipuks, Ittinee; Rattanadilok Na Phuket, Wipada; Kaewjungate, Wuttinun (Srinakharinwirot Research and Development Journal of Humanities and Social Sciences, 2022)
The objective of this article is to study elements and persuasive language strategies in BMTA bus and BMTA private joint bus advertising. The data were collected from consumer goods category advertisements that installed outside the BMTA bus and BMTA private joint bus advertising in 2018 and 2019, total of 90 advertisements. The results showed that there are 4 elements in the BMTA bus and BMTA private joint bus advertising: Copy, Image and Description, Slogan and More information. Persuasive language strategies is divided into 2 major categories which are 1. Verbal strategies found 6 sub-strategies: Lexical selection, Claiming technique, Exaggeration, Presupposition, Metaphor and Rhetorical questions. 2. Nonverbal strategies found 2 sub-strategies: Image and Color. The results of research show that elements and language strategies in the BMTA bus and BMTA private joint bus advertising are essential tools to convince consumers on the road.